Urban dynamics. Conflicts, representations, appropriations and policies. - (:unkn) unknown (Lang, 2018)
This book compiles the proceedings of the International Symposium "Urban Dynamics: Global Perspectives for Socio-Cultural Urban Management", which took place in Paris in March 2016. Professors and (post-)graduate students from a consortium of five universities, together with urban specialists, discussed diverse topics regarding European and Latin American urban societies, their dynamic processes and future challenges from an interdisciplinary perspective. The selected articles in English, French and Spanish deal with public space, urban heritage production, urban social management, citizen re-appropriation of the city, cultural and artistic practices in urban space, migrations, imaginaries, identities as well as literary cartographies of urban spaces.
Keywords: Stadtsoziologie; Stadtpolitik; Stadtentwicklungspolitik; Öffentlichkeit; Stadtbewohner; Öffentlicher Raum; Urbanität; Urbanismus; Stadtgesellschaft; Sozialer Konflikt; Stadt; Aneignung; Raumaneignung; Stadtkultur; Repräsentation; Graffiti; Randgruppe; Wohnen; Sozialwohnung; Vorstadt; Kunst im Raum